Lithuanian Sports Information Centre
Website of the Lithuanian Sports Information Centre in Vilnius which has been established in 1997. The main aims of the activities of the Centre are to take care of the systematic information about achievements of Lithuania and foreign countries in the area of physical education and sports; to create possibilities for everyone working in the area of sports to use this information.